KARAKTERISASI SELULASE TERMOSTABIL ASAL ISOLAT BAKTERI TANAH PERTANIAN PASANG SURUT - Rini Sahrida Lestari; Hasrul Satria Nur; Witiyasti Imaningsih (Bioscientiae, 2024)
Cellulase is an enzyme that can break up β - (1→4) glycosidic bonds of cellulose. Generally, cellulases are classified into three major groups, i.e., endoglucanase (EC 3.2.1.4), exoglucanase (EC 3.2.1 .91), and β glucosidase (EC 3.2.1.21). Meanwhile, five isolates of tidal swamp soil have been isolated; thus, in this research step, we are acquainted with cellulase activity and the characterization of cellulase enzymes on various temperatures, pH, and specific substrates. The activity of an enzyme was measured using the modified Miller and Bradford methods to detect the specific characteristics of the isolate. The results showed that five isolates namely ATP-1 BKP-5, HAMML-2, PKL-2, and SPBKK-3 have activities 0.025 nKat.ml-1, 0.032 nKat.ml-1, 0.296 nKat.ml-1, 0.114 nKat.ml-1, and 0.087 nKat.ml-1, respectively. Furthermore, cellulase from isolates ATP 1, BKP-5, and PKL 2 have an optimum activity at pH 7,0; 50 oC. The isolate HAMML-2 has an optimum activity at pH 5,0; 60 oC. SPBK 3 has an optimum activity at pH 5,0; 50 oC. All of those isolates can degrade CMC, Avicell, and Whatman paper No.1 and retain the activity relative to the temperatures 50 and 60 0C as the characteristics of the thermostable enzyme.